Efficacy of Oroxylin A in ameliorating renal fibrosis with emphasis on Sirt1 activation and TGF-β/Smad3 pathway modulation - Li, Guangzhuang; Xian, Sentao; Cheng, Xianchao; Hou, Yunhua; Jia, Wenqing; Ma, Yukui (Frontiers in Pharmacology, 2024)
Oroxylin A (OA) exhibits a range of biological activities. However, its specific role in renal fibrosis remains unknown. The tolerance of osteoarthritis (OA) and its impact on renal fibrosis were studied through ADMET, Lipinski filter, establishment of unilateral ureteral obstruction (UUO) model, and molecular docking, OA has good drug tolerance. Compared with the sham group, UUO mice that did not receive OA treatment showed severe tubular dilation and atrophy, ECM deposition, and inflammatory cell infiltration in their kidneys, while OA treated mice showed significant improvement in these symptoms. OA treatment remarkably restrained the accumulation of fibronectin and α-SMA. Moreover, OA treatment remarkably decreased the abnormal upregulation of inflammatory factors (IL-1β, IL-6, and TNF-α) in the obstructed kidney of UUO mice. Sirt1 expression was markedly diminished in the kidneys of UUO mice and TGF-β1-induced HK-2 cells, whereas this reduction was largely reversed after OA treatment. The results together support that OA exerts the anti-fibrotic effect partly through promoting the activity of Sirt1. In vitro results, OA treatment markedly inhibited the activation of Smad3 in UUO mice, thereby ameliorating renal fibrosis. OA could form hydrogen bonds with key amino acids ASN226 in the Sirt1, thereby activating the Sirt1, which might also be the reason why OA could resist renal fibrosis. Our study indicated that OA might exert anti-renal fibrosis effects through the activation of Sirt1 and suppression of the TGF-β/Smad3 signaling pathway.